In Vivo 7T MR Quantitative Susceptibility Mapping Reveals Opposite Susceptibility Contrast between Cortical and White Matter Lesions in Multiple Sclerosis - Bian, W.; Tranvinh, E.; Tourdias, T.; Han, M.; Liu, T.; Wang, Y.; Rutt, B.; Zeineh, M.M. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Magnetic susceptibility measured with quantitative susceptibility mapping has been proposed as a biomarker for demyelination and inflammation in patients with MS, but investigations have mostly been on white matter lesions. A detailed characterization of cortical lesions has not been performed. The purpose of this study was to evaluate magnetic susceptibility in both cortical and WM lesions in MS by using quantitative susceptibility mapping.MATERIALS AND METHODS: Fourteen patients with MS were scanned on a 7T MR imaging scanner with T1-, T2-, and T2*-weighted sequences. The T2*-weighted sequence was used to perform quantitative susceptibility mapping and generate tissue susceptibility maps. The susceptibility contrast of a lesion was quantified as the relative susceptibility between the lesion and its adjacent normal-appearing parenchyma. The susceptibility difference between cortical and WM lesions was assessed by using a t test.RESULTS: The mean relative susceptibility was significantly negative for cortical lesions (P < 10−7) but positive for WM lesions (P < 10−22). A similar pattern was also observed in the cortical (P = .054) and WM portions (P = .043) of mixed lesions.CONCLUSIONS: The negative susceptibility in cortical lesions suggests that iron loss dominates the susceptibility contrast in cortical lesions. The opposite susceptibility contrast between cortical and WM lesions may reflect both their structural (degree of myelination) and pathologic (degree of inflammation) differences, in which the latter may lead to a faster release of iron in cortical lesions.MPFLAIRmagnetization-prepared fluid-attenuated inversion recoveryQSMquantitative susceptibility mapping